Numerical Modeling Shows Increased Fracturing Due to Melt-Undercutting Prior to Major Calving at Bowdoin Glacier - van Dongen, Eef C. H.; Åström, Jan A.; Jouvet, Guillaume; Todd, Joe; Benn, Douglas I.; Funk, Martin (Frontiers in Earth Science, 2020)
Projections of future ice sheet mass loss and thus sea-level rise rely on the parametrization of iceberg calving in ice sheet models. The interconnection between submarine melt-induced undercutting and calving is still poorly understood, which makes predicted contributions of tidewater glaciers to sea level rise uncertain. Here, we compare detailed 3-D simulations of fracture initiation obtained with the Helsinki Discrete Element Model (HiDEM) to observations, prior to a major calving event at Bowdoin Glacier, Northwest Greenland. Observations of a plume surfacing at the calving location suggest that local melt-undercutting influenced the size of the major calving event. Therefore, several experiments are conducted with various local and distributed (front-wide) undercut geometries. Although the number of undercut experiments is limited by computational requirements, one of the conjectured undercut geometries reproduces the crevasse leading to the observed major calving event in great detail. Our simulations show that undercutting leads to initiation of wider fractures more than 100 m upstream of the terminus, well beyond the directly undercut region. When combining a moderate distributed undercut with local amplified undercuts at the two observed plumes, fracture initiation also increases in between the local undercuts. Thus, our results agree with previous studies suggesting the existence of a 'calving amplifier' effect by submarine melt, both upglacier and across-glacier. Consequently, the simulations show the potentially large impact of submarine melt-induced undercutting on iceberg size.